Central composite design optimization of active and physical properties of food packaging films based on chitosan/gelatin/pomegranate peel extract - Bertolo, Mirella Romanelli Vicente; Dias, Lucas Danilo; Oliveira Filho, Josemar Gonçalves de [UNESP]; Alves, Fernanda; Marangon, Crisiane Aparecida; Amaro Martins, Virginia da Conceição; Ferreira, Marcos David; Bagnato, Vanderlei Salvador; Guzzi Plepis, Ana Maria de; Bogusz, Stanislau (Elsevier, 2022)
Chitosan and gelatin-based materials containing pomegranate peel extract were prepared for potential application as food packaging materials. An optimized composition of 0.8% chitosan, 0.2% gelatin and 1 mg g-1 of extract was chosen with the aid of a central composite design, presenting low viscosity (8.36 ± 0.20 Pa s) and solubility (26.00 ± 5.50%), as well as an expressive inhibition halo against Botrytis cinerea (6.17 ± 0.36 mm). The interaction between the polymeric matrix and the extract was confirmed by spectroscopic and morphological analysis. Rheologically, the optimized formulation was more resistant to deformation and shear (activation energy increased by almost 5 kJ mol-1) than the formulation without the extract. The use of pomegranate peel extract changed the film color, reduced its solubility (by more than 5%), increased mechanical resistance (tensile strength increased by 15 mPa), and improved light barrier properties by 30%. The extract also imparted antioxidant activity to the film, which was able to inhibit 20% of DPPH (2,2-diphenyl-1-picrylhydrazyl) radical at 38 mg mL-1. The optimized composition also showed inhibitory bacterial properties (31.2 and 125 µg mL-1) against S. aureus and S. enteritidis, respectively. Thus, the optimized film exhibited interesting characteristics for food packaging applications, many of them brought by the use of pomegranate peel extract, which highlights the valuable contribution of this agro-industrial waste to the properties of the polymeric films.
Keywords: Chitosan; Gelatin; Multivariate optimization; Packaging film; Pomegranate peel extract